Índice de valor de importancia del bosque de colina baja en la concesión forestal 16-rq/c-j-036-04, distrito de Alto Tapiche, Loreto, Perú. 2023 - López Pacaya, Alfredo (2025)
The research was carried out in the low hill forest belonging to the forest concession 16-RQ/C-J-036-04, located in the district of Alto Tapiche, Loreto, Peru. This ecosystem hosts 465 trees, distributed in 8 commercial species of 6 families and 8 genera, reflecting a remarkable diversity. The Fabaceae stand out with Cedrelinga catenaeformis and Copaifera paupera, which represent 61.29% of the total number of individuals, demonstrating the need for management that combines the sustainable use of the dominant species with the protection of the less common ones. The average timber volume reached 4,291 m³/ha, with Cedrelinga catenaeformis (tornillo) leading with 2,005 m³/ha (46.7%), concentrated in large diameter trees (120 cm or more). In contrast, Virola albidiflora (cumala caupuri) has the lowest volume, with only 0.032 m³/ha. Larger trees account for 47.7% of the total volume, while those with smaller diameters contribute 27.4%. The Importance Value Index (IVI) highlights Cedrelinga catenaeformis as the most outstanding species, with an IVI of 116.64, thanks to its high dominance and distribution, while Virola albidiflora appears as the least relevant, with an IVI of 7.42. These results confirm significant differences in the horizontal structure of the species, highlighting the diversity of the ecosystem and the need for sustainable management strategies that consider these variations.